Análisis de la cadena de suministro de una empresa abastecedora de - Baquerizo, Guillermo (2010)
Following the pattern of large commercial development experienced by the Insular Region in recent years, this investigation will be a first approach to the problem of food supply to the province of Galapagos, through the elaboration and selection of a forecasting sales model, determination, improving and monitoring the level of service, and analysis of financial ratios to research the diagnostic supply chain in a Guayaquil-based company that supplies the Galapagos Islands with food.